The Influence of Workload, Work Environment and Organizational Communication on Employee Performance at the Badan Amil Zakat Nasional (Baznas) in Surabaya City - Novita Rosalina; M Sihab Ridwan (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
This study aims to determine partially or simultaneously the independent variables of Workload, Work Environment, and Organizational Communication with the dependent variable of Employee Performance at the National Amil Zakat Agency (BAZNAS) of Surabaya City. The population in this study were all employees of BAZNAS Surabaya City, totaling 40 people. The sample in this study was taken using saturated sample technique. The data collection technique in this study was a survey technique with a questionnaire instrument. Data analysis in this study used validity test, reliability test, classical assumption test, multiple linear regression analysis and coefficient of determination (R2), while hypothesis testing techniques used t test and F test by utilizing SPSS version 26 program. Workload partially has a significant negative effect on Employee Performance, Work Environment partially has a positive and significant effect on Employee Performance, Organizational Communication partially has a positive and significant effect on Employee Performance. Simultaneously, Workload, Work Environment, and Communication variables have a significant effect on Employee Performance.